2014
DOI: 10.1002/cne.23552
|View full text |Cite
|
Sign up to set email alerts
|

DSCAM localization and function at the mouse cone synapse

Abstract: The Down Syndrome Cell Adhesion Molecule (DSCAM) is required for regulation of cell number, soma spacing and cell type specific dendrite avoidance in many types of retinal ganglion and amacrine cells. In this study we assay the organization of cells making up the outer plexiform layer of the retina in the absence of Dscam. Some types of OFF bipolar cells, type 3b and type 4 bipolar cells, had defects in dendrite arborization in the Dscam mutant retina, while other cell types appeared similar to wild type. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…From E12.5 through to postnatal ages Dscam is expressed strongly by most, if not all, RGCs (5). Double immunofluorescent staining of cultured P0 retinal ganglion cells with antibodies validated previously against DSCAM (12)(13)(14) and neurofilament confirmed that DSCAM localized to retinal axons, with expression concentrated at the growth cone (Fig. 1A, white arrowhead).…”
Section: Resultssupporting
confidence: 78%
“…From E12.5 through to postnatal ages Dscam is expressed strongly by most, if not all, RGCs (5). Double immunofluorescent staining of cultured P0 retinal ganglion cells with antibodies validated previously against DSCAM (12)(13)(14) and neurofilament confirmed that DSCAM localized to retinal axons, with expression concentrated at the growth cone (Fig. 1A, white arrowhead).…”
Section: Resultssupporting
confidence: 78%
“…Surprisingly, many of these factors appear to function through repulsion, that is by preventing interactions, rather than promoting them. This list would include DSCAM and sidekick proteins, MEGF proteins, the γ-protocadherin, semaphorins and plexins (de Andrade et al, 2014; Fuerst et al, 2009; Fuerst et al, 2008; Kay et al, 2012; Lefebvre et al, 2012; Matsuoka et al, 2011; Yamagata and Sanes, 2008). While neurexins and neuroligins are required for synaptic pairing, the limited diversity of neuroligins in the mouse retina suggests that other factors are playing a role in promoting adhesion (Ichtchenko et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously characterized the role of the DSCAM at the cone synapse and found that if facilitates organization of several types of bipolar cells (de Andrade et al, 2014). Mammalian Dscams lack the splice diversity of fly Dscams and the role of providing this diversity may be subsumed by the protocadherins in the vertebrate (Sanes and Zipursky, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Nearest neighbor analysis was performed as previously described using the program winDRP (de Andrade et al, 2014; Keeley and Reese, 2014; Rockhill et al, 2000; Wassle and Riemann, 1978). Soma size was set at 10 μm, with 25 10 μm bins selected for analysis.…”
Section: Methodsmentioning
confidence: 99%